2018
DOI: 10.15294/biosaintifika.v10i3.15356
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ganoderma lucidum Extract on Diabetic Rats

Abstract: Diabetes mellitus (DM) is a metabolic syndrome which occurs when insulin is insufficiently produced or insulin cannot well serve its function. Diabetes is marked with increase in blood glucose level followed by increase in glycosylated hemoglobin level and decrease in insulin level. This research aims to examining the effect of Ganoderma lucidum extract on the blood glucose, insulin and glycosylated hemoglobin (HbA1c) level of diabetic white rat and determining the most effective dose of extract to be a diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 9 publications
0
10
0
1
Order By: Relevance
“…Earlier studies show that mushrooms are rich in ß-D-glucans, ß-glucan, a type of dietary fiber that shows promising health benefits against T2DM [80]. Mushroom extracts from Pleurotus species [56], Boletu [58], Grifola frondosa [81], Agaricus bisporus [38], Hericium erinaceus [63], and Ganoderma lucidum [82] regulate the synthesis of glycogen and lowers blood glucose levels by regulating gene expression of glycogen synthase kinase (GSK-3 ß), glycogen synthase (GS) and glucose transporter 4 (GLUT4) in liver and muscle. Therefore GSK-3 ß could be identified as an insulin-mediated GSregulated negative regulator [83].…”
Section: Blood Glucose-lowering Effect Of Polysaccharidementioning
confidence: 99%
“…Earlier studies show that mushrooms are rich in ß-D-glucans, ß-glucan, a type of dietary fiber that shows promising health benefits against T2DM [80]. Mushroom extracts from Pleurotus species [56], Boletu [58], Grifola frondosa [81], Agaricus bisporus [38], Hericium erinaceus [63], and Ganoderma lucidum [82] regulate the synthesis of glycogen and lowers blood glucose levels by regulating gene expression of glycogen synthase kinase (GSK-3 ß), glycogen synthase (GS) and glucose transporter 4 (GLUT4) in liver and muscle. Therefore GSK-3 ß could be identified as an insulin-mediated GSregulated negative regulator [83].…”
Section: Blood Glucose-lowering Effect Of Polysaccharidementioning
confidence: 99%
“…A hypoglycaemic effect was also observed following administration of an alcoholic extract of G. lucidum (250, 500, and 1000 mg/kg) given for 14 days in alloxan-induced diabetic rats (Ratnaningtyas et al. 2018 ). Another recent study in streptozotocin-induced diabetic rats showed that a hydroethanolic extract of G. lucidum containing β-glucan, proteins, and phenols, reduced plasma glucose and lipid levels through preservation of pancreatic islets (Bach et al.…”
Section: Health Benefits Of G Lucidummentioning
confidence: 93%
“…Mycelial extract of Pleurotus ostreatus was noticed to reduce the serum glucose level in streptozotocin-induced diabetes mellitus in rats [34]. Ganoderma lucidum ethanol extract of powdered fruiting bodies reduce serum glucose in white rats [35]. Also, water and 80% ethanol extracts of fruiting bodies of Ganoderma lucidum decreased glucose level in serum of streptozotocin-induced diabetic rats [36].…”
Section: Antidiabetic Activity Of Mushroomsmentioning
confidence: 99%